A Fresh Look at "Belial" in Biblical Hermeneutics and Postbiblical Literature - Agra, Toochukwu S. (Biblical research, 2023)
While the precise origin, meaning, and etymology of the term "Belial" (בליעל) in the Hebrew Bible has been a subject of considerable debate, there is no doubt that it exercised significant influence on the progress of Jewish thought. From the third century BCE onwards, Belial ( or Beliar in Greek texts) seems to have developed into a proper name for Satan (an idea not found in the HB) and become the leader of the forces of darkness and evil, a notion that pervades pseudepigraphic and Qumran writings. In the Dead Sea Scrolls, Belial heads the forces of darkness as their military leader against the lot of God in the eschatological war. This raises a few questions which this paper seeks to address: How did an idea found in the HB as qualifying an evil character or disposition evolve into a diabolical figure in later Jewish thought? How did the term originate? What accounts for the various nuances and interpretations in later Jewish literature?